Design and experiment of low-frequency ultrasonic nozzle integrating air-assistant system and acoustic levitation mechanism - Gao, Jianmin; Tunio, Mazhar Hussian; Chen, Yiming; He, Rui (International Journal of Agricultural and Biological Engineering, 2020)
Ultrasonic atomization nozzles are generally divided into two categories: high frequency and low-frequency ultrasonic atomization nozzles. Compared with high-frequency ultrasonic atomization nozzles (working frequencies>1 MHz), low-frequency ultrasonic atomization nozzles are not sensitive to clarity, temperature and viscosity of the liquid. However, they can control atomization quantity precisely, but the sizes of droplets generated by them are relatively large. In aeroponics cultivation, and precision welding, in such both cases, precise spraying control and tiny droplet sizes are expected. Therefore, how to decrease droplet size using low-frequency ultrasonic atomization nozzles is a valuable issue. In this paper a 60 kHz low-frequency ultrasonic atomization nozzle integrating air-assistant system and acoustic levitation mechanism was proposed and designed. Furthermore, the design was verified by FEA (Finite Element Analyzes) and impedance analyzer PV70A, and the verified results indicated relative design error was 0.49%. Driving voltage, spout angle, air pressure and levitating ball were taken as influential factors in the experimental protocol to the character in spray properties of this designed nozzle. A laser particle size analyzer was used to measure droplet sizes. Experiment results indicated that: the diameters of droplets generated by this nozzle at driving voltage 46 V were smaller than those at 40 V driving voltage; Both the assistant air and levitation mechanism could effectively change the diameters and uniformity of droplets; The minimum values of D10, D50, and D90 (D10, D50 and D90 were mean diameters when cumulative percentages of the samples’ diameter were 10%, 50% and 90%, respectively) were 23.06 µm, 31.14 µm and 41.38 µm, respectively. However, all those minimum values were presented at the same run (spout angle 0°, air pressure 0.05 MPa, having levitated ball, driving voltage 46 V); Levitating ball above the atomization surface would make droplet sizes more uniform and tinier. More importantly, the famous Lang equation which assumes that droplet diameters just decided by the liquid surface tension, density and ultrasonic atomizer’s working frequency needed to be revised because experimental results indicated that changing vibration amplitudes of ultrasonic atomization surface might lead to the changing of the droplet diameters and those results were at odds with the Lang equation. Keywords: nozzle, ultrasonic atomization, droplet, sonic levitation, air-assistant DOI: 10.25165/j.ijabe.20201306.5419 Citation: Gao J M, Hussian Tunio M, Chen Y M, He R. Design and experiment of low-frequency ultrasonic nozzle integrating air-assistant system and acoustic levitation mechanism. Int J Agric & Biol Eng, 2020; 13(6): 25–33.